A study to evaluate the effectiveness of local cold application on pain response during intravenous cannula insertion among children 6-12 years admitted in selected hospitals at Indore - Daya, Ruhi Prerna; Pandey, Prerna; Daya, Morin Joy (International Journal of Research in Medical Sciences, 2023)
Background: Hospitalized children commonly experience pain and anxiety as the most prevalent adverse stimuli. One of the most alarming and distressing causes of pain and anxiety that is frequently reported is venipuncture. The objective of this study was to evaluate the impact of cold and thermomechanical stimulation on pain and anxiety levels experienced by pediatric patients during intravenous (i.v.) cannulation. Methods: This study aimed to assess the efficacy of cold and thermo mechanical stimulation in reducing anxiety and pain experienced by children during intravenous (i.v.) cannulation through a prospective case-control design. Children age 3-12 years and requiring i.v. cannulation were included. Children’s level of anxiety and pain was assessed using the children’s fear scale (CFS) and Wong-Baker faces pain scale (WBFS). Results: Mean scores of the self- reported procedural level of pain were less in the intervention group as compared to the control group (2.80±1.86, 7.47±2.40). Median of procedural pain level showed a significant difference between the intervention and control group at p<0.001, inferring that the cold and thermomechanical strongly resulted in a reduction of perception of pain during the cannulation procedure. Conclusions: The research provided evidence in favor of the cold and thermomechanical as a promising non-pharmacological intervention for pain reduction during the process of intravenous cannulation.